History of Human Ecology Institutions in Poland - Wolański, Napoleon; Siniarska, Anna (Studia Ecologiae et Bioethicae, 2003)
Poland is the country where a first scientific institution under the name of Human Ecology (HE) had been established. It took place in 1960 in the National Research Institute of Mother and Child. In 1969 this institution was moved to the Institute of Ecology of the Polish Academy of Sciences under the name of Laboratory of Human Ecology then changed into the Department of Human Ecology. In the middle of the 60s, the Laboratory of Human Ecology and Paleopathology was created in the Department of Mediterranean Archaeology of the Polish Academy of Sciences. In the 70s the Department of Hygiene and Human Ecology existed in the College of Physical Education in Katowice. HE is the main interest of the Department of Human Populational Ecology, Institute of Anthropology of the Adam Mickiewicz University in Poznań. Since 1999 the Division of Human Ecology within the Department of Biology and Human Ecology exists in the Academy of Physical Education in Wrocław. In 2000 the Department of HC in the Institute of Ecology of the Polish Academy of Sciences was canceled and then in 2001, the Unit of EC in the Faculty of Christian Philosophy of the Cardinal Stefan Wyszynski University was created. Within this Unit, two Chairs were formed: Human Biology and Cultural Anthropology. The first one contains three Departments: 1. Auxology and Gerontology; 2. Genetics of Human Population and Demography; 3. Public Health and Nutrition. The second Chair has two Departments: 1. Ethnology and Anthropogeography; 2. Urban and Space Planning.